Pregnant Women Chronically Infected by Toxoplasma gondii with Depressive Disorder: Differential Modulation of Pro-Inflammatory and Anti-Inflammatory Cytokines - Carolina Salomão Lopes; Ricardo José Victal Carvalho; Tamires Lopes da Silva; Heber Leão Silva Barros; Lucas Vasconcelos Soares Costa; Danielly Christine Adriani Maia Mota; Bellisa Freitas Barbosa; Luan Souza Vieira; Talyene Marques de Araújo; Alírio Resende Costa; Ruth Opeyemi Awoyinka; Tiago Wilson Patriarca Mineo; et al. (Pathogens)
Depressive disorder during pregnancy is a common condition, affecting approximately 10–15% of pregnant women, and is associated with adverse pregnancy outcomes such as inadequate prenatal care, substance abuse, and fetal growth restriction. Beyond neurotransmitter disturbances, increasing evidence suggests that infectious agents may play a role in the pathophysiology of depression through immune system modulation. Toxoplasma gondii infection has been linked to various mental disorders in the general population, including depression and anxiety. This study aimed to investigate whether depressive disorder during pregnancy is associated with chronic T. gondii infection by analyzing cytokine levels involved in inflammatory response modulation. Serum levels of TNF, IFN-γ, TGF-β1, IL-6, IL-8, IL-10, and MIF were measured in 79 pregnant women (18–40 years old) during the third trimester of an uncomplicated pregnancy. Participants were divided into four groups: Group I—depressive disorder and T. gondii seropositive (n = 19); Group II—no depressive disorder and T. gondii seropositive (n = 20); Group III—depressive disorder and T. gondii seronegative (n = 20); and Group IV—no depressive disorder and T. gondii seronegative (n = 20). Depressive symptoms were assessed using the Edinburgh Postnatal Depression Scale (EPDS) during routine prenatal visits, and blood samples were collected during standard prenatal examinations. Significant differences in cytokine levels were observed among the study groups. Notably, the group with both depressive disorder and chronic T. gondii infection exhibited a distinct cytokine profile characterized by significantly elevated TNF, IL-6, and IL-10 levels and significantly reduced IL-8 and MIF levels compared to the other groups. These findings suggest that pregnant women with depressive disorder and chronic T. gondii infection exhibit an altered balance of pro- and anti-inflammatory cytokines. This is the first study to investigate the association between serum cytokine levels, depressive disorder, and chronic T. gondii infection in pregnant women. Further research is needed to evaluate the potential of these immunobiomarkers as diagnostic tools or for monitoring therapeutic and prognostic strategies in this context.